Strengthening Coastal Cities and Building Climate Resilience Against Climate Change: Policy Pathways for the Global South - Islam, Karem Rouby; Abdalla Ragab, Rokaya Ragab; Septian, Rizky Tri (Public Policy Journal, 2025)
In the face of escalating climate change impacts, improving resilience for coastal cities in the Global South is important to protect the lives and livelihoods of millions of people living in vulnerable urban areas. This research aims to provide a series of recommendations to enhance the resilience of coastal cities in the Global South against climate change. This study uses a comprehensive approach that combines case study analysis, literature review, and policy recommendations, focusing on coastal cities in the Global South, such as Alexandria, Cape Town, and Dakar, to examine the impacts of climate change, including sea level rise, flooding, and coastal erosion. The research also draws on existing climate policy frameworks, such as the Paris Agreement and regional initiatives, to formulate practical policy recommendations.  The findings showed that increasing budgets and investment in urban resilience are critical to supporting the implementation of adaptation measures, including infrastructure upgrades, ecosystem restoration, and community resilience initiatives. Collaboration and the strengthening of governance capacities at the local and national levels are also essential for effective adaptation planning and implementation. In addition, building networks among coastal cities in the Global South is vital for sharing knowledge, exchanging best practices, and fostering solidarity among urban areas facing similar challenges.